(untitled) (Baghdad Science Journal, 2011)
The foreguts of a total of 515 fish of Chondrostoma regium (Heckel, 1843) (locally: Bala’aot Malloky) were studied. These fish were collected from Tigris River at Salah Al-Deen Province (between Al-Hagag & Yathrib) for 20 months between March and October of the next year. Detritus, plant in origin materials (19.6%, 23.0% & 24.9%); green and blue green algae, mostly Cladophora, Cosmarium and Merismpedia sp. (17.1%, 12.9% & 12.2%) and diatoms, mostly Diatoma, Chanathes, Amphora and Cyulbella sp. (16.9%, 8.8% & 8.2%) were the main food categories taken by these fishes according to occurrence (O%), volumetric methods (V%) and ranking index (R%). Debris (not part of the diet) took 45.3% of the studied fish foreguts by volume. Detritus was also the most important food category (25.9%, 18.2%, 22.9% & 19.8%, by ranking index) at all sampling stations respectively, and taken by different fish size groups (168-200, 201-300 & 301-350mm).The diet overlaps between these fish size groups and that between different sampling stations were ranged between 0.86-1.0, i.e. fish were mainly feeding on the same food organisms.